PANDANGAN MASYARAKAT GRESIK TERHADAP POLITIK UANG DALAM PEMBAGIAN BANSOS - Sabrina, Shafa; Ballo, Fin Fina Marsita Ziporani Daniela; Asi, Alfina Christya Eka; Saksono, Ken Achmad (Bawaslu Provinsi Jawa Barat, 2024)
This research aims to analyze cases of money politics through the distribution of social assistance in the elections in Gresik and find out whether this action is in line with the principles of Pancasila. The method used in this research is qualitative research using a questionnaire for data collection. The questionnaire was distributed to respondents who were residents of the Gresik area. The research results show that money politics through the distribution of social assistance often occurs in elections because regulations to prevent these actions are still less effective. Money politics regarding the distribution of social assistance is considered incompatible with Pancasila. So action or solutions are needed to overcome the practice of money politics in distributing social assistance during the election period. This research explains and describes the perspectives of the people of Gresik on the practice of money politics in elections and money politics on the principles of Pancasila.